ROLE OF NEEDS AND REASONS FOR TERRITORIAL ORGANIZATION OF SOCIAL LIFE (Proceedings of the YSU C: Geological and Geographical Sciences, 2024)
Service sphere has its main role in the organization of social life. Due to it, human gets satisfaction for his or her needs. And for organization of such system, it is important to explore and estimate its scientific mechanism. So, it gives opportunity to estimate social life and needs cooperation.
Keywords: motivation; needs; territorial organization; social life; regional system; remuneration